THE EFFECT OF INSTRUCTIONAL APPROACH AND VERBAL REASONING ON STUDENTS’ ENGLISH SPEAKING COMPETENCE, SMA NEGERI 14 AND 21 MEDAN - NAEKLAN SIMBOLON (FIP Unimed, 2013)
ABSTRACT The objective of this research was to know the effect of instructional approach and verbal reasoning on students’ English speaking competence SMA Negeri 14 and 21 Medan.The research was conducted at SMA Negeri 14 and 21 Medan, in the first semester 2012/2013 academic year. The experimental research is done by using 2 x 2. Treatment by level design, with 80 students as sample that were taken by random sampling. The instruments used were verbal reasoning test and English speaking competence observation. The result of the research shows that: 1) there is the difference of students’ speaking competence between students taught by Contextual Teaching and Learning and conventional instruction; 2) there is the interaction between instruction approach and verbal reasoning and speaking English competence of SMA Negeri 14 and 21 Medan; 3) there is the difference of the students’ English speaking competence between students who have high verbal reasoning and low verbal reasoning; 4) there is the difference of the studens’ English Speaking Competence who have low verbal reasoning taught by using Contextual Teaching and Learning compare with the students who taught by using conventional instruction. Keywords: Contextual teaching and learning, verbal reasoning, English speaking competence.